Effect of different antagonist rhizobacteria and neem products on club root of crucifers - M. PRAMANIK, I. BHA ITACHARYA and (Indian Phytopathology, 2002)
The antagonist bacterial strains, namely, Bacillus subtilis T99, Pseudomonas fluorescens H237, StreptomycesÂ  graminofaciens GIll and 2% neem oil suspension were tested under laboratory and glass house conditions to see the effect on two phases of colonization by Plasmodiophora brassicae (Woronin) primary phase (root hair infection) and secondary phase (club formation) on Chinese cabbage, Of the three antagonists tested, Pseudomonas fluorescens and Streptomyces graminofaciens reduced size and growth of club as well as rate of root hair infection process. Interestingly, Bacillus subtilis stimulated rate of root hair infection and club formation, and 2% neem oil suspension drastically reduced both. In a field trial, neem oil was found phytotoxic when applied as soil drench and neem cake and nimin reduced disease severity significantly.